Genomic Analysis of Consecutive Acinetobacter baumannii Strains From a Single Patient - Kim, Sun Ju; Kim, Yae-Jean; Ko, Kwan Soo (Frontiers in Microbiology, 2018)
Acinetobacter baumannii is one of the most important nosocomial pathogens, and thus it is required to investigate how it disseminate in hospitals and infect patients. We performed whole genome sequencing for 24 A. baumannii strains isolated successively from the blood of a single patient to evaluate whether repeated infections were due to re-infection or relapse infection and to investigate within-host evolution. The whole genome of the first strain, BL1, was sequenced de novo using the PacBio RSII system. BL2–BL24, were sequenced with an Illumina Hiseq4000 and mapped to the genome sequences of BL1. We identified 42 single-nucleotide variations among the strains. The SNVs differentiated the strains into three groups, BL1, BL2–BL16, and BL17–BL24, indicating that the patient suffered from re-infections or co-infections by similar, but different strains. The results also showed that A. baumannii strains in each group were rather stable at the genomic level. Our study emphasizes the importance of intensive infection control.